Contemporary challenges to EU legality - Kilpatrick, Claire; Scott, Joanne, 1965- (Collected courses of the Academy of European Law ;, 2021)
This book focuses on contemporary challenges to EU legality. It includes a theoretical perspective and delves into many substantive areas of EU law, including Brexit, migration, and the sovereign debt crisis.